Police officer transitions to retirement in the United Kingdom: social identity, social support, and (in)justice - Bullock, Karen (Policing and society, 2020)
This article draws on qualitative interviews to examine police officers’ experiences of transitioning to retirement in the United Kingdom, a matter that has been hitherto under researched. We find that the well-established routines and the social identity conferred by the police role are severed at retirement and the transition to retirement may be experienced as disruptive. This has implications for self-esteem, access to support, and perceptions of fairness of the organisation. However, we further argue that retirement is a multidimensional concept and experienced differently, depending on the context and circumstances in which it occurs. When officers are underprepared or retired for medical reasons, the transition was especially disruptive. The article makes important contributions to the literature on police officer social identity, well-being, and organisational justice.